Renal handling of iodobenzoates in rats - Laznicek, M; Laznickova, A (The Journal of pharmacy and pharmacology, 1999)
Renal elimination pathways of three positional isomers of iodobenzoic acid (2-iodobenzoate, 3-iodobenzoate and 4-iodobenzoate radiolabelled with 125I) were compared using the perfused rat kidney in-situ. All agents were eliminated both in a parent form (involving all renal elimination mechanisms i.e. glomerular filtration, tubular secretion, and tubular reabsorption) and also metabolized to a large extent in the kidney. After 3-iodobenzoate and 4-iodobenzoate administration, the major fractions of radioactivity found in urine were in the form of their metabolites, whereas 2-iodobenzoate was eliminated into urine mostly as the parent compound. Proportions of the individual metabolites in the urine of the perfused rat kidney were similar to those in intact rats for all agents. The results suggest that the kidney is the major organ for both the excretion and metabolism of iodobenzoates in rats. The principal renal metabolic reaction for all compounds under study was conjugation with glycine to produce the corresponding hippuric acid derivatives.
Keywords: Animals; Kidney; Iodobenzoates; Rats, Wistar; metabolická clearance; Glomerular Filtration Rate; Structure-Activity Relationship; jodbenzoáty; chromatografie na tenké vrstvě; renální oběh; injekce intravenózní; Male; Metabolic Clearance Rate; Renal Circulation; biotransformace; krysa rodu Rattus; vztahy mezi strukturou a aktivitou; Biotransformation; zvířata; mužské pohlaví; Chromatography, Thin Layer; ledviny; Rats; hodnoty glomerulární filtrace; Injections, Intravenous; potkani Wistar